Spatial Analysis of Stunting Prevalence in Ambalawi District, Bima - Iksan, Muammar; Apriansyah, Muh.; Alkhair, Alkhair (Persatuan Dosen Kesehatan Masyarakat, 2025)
Stunting is a chronic nutritional problem that affects children's growth and development, particularly in areas with limited access to healthcare services and nutritious food. This study aims to analyze the trend of stunting prevalence in Ambalawi District, Bima Regency, from 2020 to 2022 and examine its spatial distribution based on severity levels in each village. The research uses secondary data analysis from Ambalawi Community Health Center (Puskesmas) reports and spatial mapping to identify the distribution patterns of stunting and trends. The findings indicate that the number of stunted children in Ambalawi District increased from 219 in 2020 to 317 in 2022. Nipa and Rite consistently fall into the high stunting category, while some villages experienced status changes, such as Tolowata, which improved from moderate to low, and Talapiti, which worsened from low to moderate. Key contributing factors to stunting in this region include limited access to healthcare services, poor dietary habits, socio-economic conditions, and inadequate sanitation. This study highlights the need for more effective and region-based interventions to sustainably reduce stunting rates, particularly in high-prevalence villages.